Salisbury Cathedral
The bay design of the nave shows little advance on that of Lincoln. The single containing arch of the triforium stage and its dark marble shafts appear in sharp contrast to the main arcade below, in a somewhat disjointed combination, which was not repeated. Flying buttresses to support the vault are concealed within.